STUDY OF INDONESIAN STINGLESS BEE PROPOLIS POTENTIAL AS ANTIOXIDANT: A REVIEW - Yanti, Evita Novi; Kustiawan, Paula Mariana (Jurnal Farmasi Sains dan Praktis, 2023)
Indonesia is known have rich biodiversity, one of that is propolis. Propolis was an abundance bee product, especially from stingless bee species. Propolis has been known to have various health benefits, such as antioxidant and can maintain the immune system. However, comprehensive information regarding this potential is not widely known. The purpose of this study was to determine the potential of propolis Trigona sp. as an antioxidant from Indonesia. This study uses a screening method in journals that have been found through the search systems of Google Scholar, PubMed, Scopus and Garuda. Classification of data was based on inclusion and exclusion by selecting research journals that do not meet the criteria. The results of the screening that have been carried out show that the flavonoid and phenolic compounds present in the propolis Trigona sp. has potential as an antioxidant. The flavonoid and phenolic compounds contained in the propolis Trigona sp. has an important role in absorbing free radicals and has the potential to be developed as a product.